Effects of AlCl3 on the Liver Function of Wistar Rats Treated with Moringa oleifera Seed Extracts - Yusufu, Dawoye; Zinas, Simon Teza; Shenia, Zephaniah Hananiah; C, Ugwuoke Kenneth; Umaru, Isaac John; Ejeh, Yakubu Ojochenemi; Grace, Onwubiko N.; Henry, Onwubiko A.; Audu, Anthony Mishara; Umaru, Kerenhappuch Isaac (Darul Yasin Al Sys, 2024)
In this study ALT and AST levels of experimental rats were significantly (p<0.05) increased from 11.91 ± 0.20 and 11.83 ± 0.40 to 57.23 ± 0.24 and 59.29 ± 0.50 respectively due to intoxication with aluminum chloride. When rats were treated with ethanol and aqueous extracts of Moringa oleifera at 100 mg/kg the levels of ALT dropped down to 11.62 ± 0.40 and 11.61 ± 0.17 respectively and the AST levels dropped to 11.39 ± 0.25 and 11.42 ± 0.15 respectively. A further increase in the concentrations of both extracts to 400 mg/kg resulted to a significant elevation of ALT 11.93 ± 0.17 (ethanol) and 11.94 ± 0.07 (aqueous) and AST 11.77 ± 0.25 (ethanol) and 11.78 ± 0.15 (aqueous). AST and ALT are common liver enzymes because of their higher concentrations in hepatocytes, but only ALT is remarkably specific for liver function. Therefore, an elevation in serum concentration of ALT is an indication of liver damage. The preliminary phytochemical screening for seed extracts of Moringa oleifera revealed that flavonoids, terpenoids, phenols, alkaloids, steroids and reducing sugars tannins were present in both the ethanol and aqueous extracts. Saponins and tannins were only found in the aqueous and ethanol extracts respectively. Experiments to observe for lethal conditions or changes in behavior showed no lethality or behavioral change at doses of 10, 100, 1000, 1600 and 2900 mg/kg bw. Weakness and drowsiness was exhibited at a dosage of 5000 mg/kg bw but no death occurred within 24 hrs. of administration.